(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: As there is currently an epidemic of type 2 diabetes mellitus (T2DM), increasing attention should be paid to diabetic retinopathy (DR), a major complication of the disease which can lead to disability and blindness. Increased levels of growth factors (mainly, vascular endothelial growth factor (VEGFA)), angiogenesis factors, and cytokines in the aqueous humor have been reported in DR. Purpose: To identify the relationship of VEGFA with the stage of DR and duration of disease in T2DM through (1) investigation of the effect of increased aqueous VEGFA level on DR complications and (2) estimation of the sensitivity of clinical and laboratory indicators to the amount of VEGFA in the aqueous humor. Materials and Methods: Totally, 302 persons (604 eyes) were included in the study. Patients with T2DM were divided into three groups according to the severity of DR: Group 1 (no retinopathy, 76 patients), Group 2 (non-proliferative DR, 64 patients), and Group 3 (proliferative DR, 64 patients). The control group included 98 individuals with no T2DM or DR. Aqueous humor VEGFA levels were measured using enzyme-linked immunosorbent assay kits from eBioscience. Statistical analyses were performed using SPSS 11.0, MedCalc v.15.11.0 and Medstat Software. Results: Regression analyses demonstrated that aqueous VEGFA level directly and significantly influences the stage of DR and diabetes duration at baseline (P = 2.27E-08 and P =6.15E-05, respectively). In addition, increased aqueous VEGFA levels significantly influence the probability of developing neovascularization in the ocular tissue, vitreous hemorrhage or PDR (P < 0.05). An increase in the probability of developing optic disc neovascularization, retinal neovascularization, vitreous hemorrhage, vitreoretinal neovascularization, or PDR occurs with an increase in aqueous VEGFA level above 992 pg/mL, 923 pg/mL, 1005 pg/mL, 1022 pg/mL; and 926 pg/mL, respectively. Conclusion: Elevated aqueous VEGFA levels are a potent pathogenic factor for progression of DR in patients with T2DM.